Bleach. 35, Higher than the moon - Kubo, Tite; Caselman, Lance (Kubo, Tite. Bleach (VIZ Media), 2011)
"While the Soul Reapers are entrenched in bloody one-on-one battles with the Espadas, their sworn enemy Aizen is preparing to make the next move in his elaborate plan. The battlefields of Hueco Mundo will soon give way to another battlefield where the price of losing will prove to be infinitely higher"--From publisher's web site.